Comparação entre sistemas de contenção de subsolo: parede diafragma e estacas justapostas - Lima, Wilton de Oliveira (Universidade Federal de São Carlos, 2021)
The process of choosing a soil retaining system for underground buildings is based on techniques and economics parameters. There are two very common soil retaining systems in Brazil: Diaphragm Walls and Bored Pile Walls. A bad choosing of that kind of solution can provoke, therefore, building pathology’s and waste. Thereby, the elaboration of a choosing directrix can be very helpful as a source of comparison between these two solutions based on representative technique parameters of the two methods. In this project, the most important technique parameters of the choosing a soil remaining system were studied and, more deeply, the construction processes of Diaphragm Walls and Bored Pile Walls. As result, this study led to the conclusion of a better viability for using Diaphragm Walls when water is present, but specially was observed the importance of knowing and considering all the parameters found.
Comparison between underground soil retaining systems: diaphragm wall and bored pile walls
Keywords: Parede-diafragma; Estacas justapostas; Contenção; Diaphragm Walls; Bored Pile Walls; Soil retaining; ENGENHARIAS::ENGENHARIA CIVIL::ESTRUTURAS